Expressão gênica e características bioquímicas de genótipos de Coffea canephora submetidos a diferentes condições hídricas - Santiliano, Fabiano Costa (2023)
Coffee is a crop of great importance to the economic scenario of Brazil and the world. With predictions of climate change, especially related to water deficit, there has been an increasing search for materials more adapted to drought. This study aimed to evaluate the molecular responses through differential gene expression of CcMPR1, RBCS1, and CcGolS1 genes, as well as the biochemical responses of 14 young progenies of C. canephora, aiming to identify genotypes with better performance under water deficit conditions. The study was conducted in a greenhouse using a randomized block design with 14 treatments (genotypes) and two factors (irrigated and deficit), divided into three blocks, totaling 84 experimental plants for molecular analyses, and divided into four blocks, totaling 112 experimental plants for biochemical analyses. These genotypes were subjected to water deficit by gradually and prolonged irrigation limitation for subsequent evaluation of the expression levels of CcMPR1, RBCS1, and CcGolS1 genes, all involved in the coffee plant's response to drought. The behavior of the genotypes was also evaluated regarding the biochemical parameters of nitrate composition, organic nitrogen, proline, and leaf phenolic compounds under irrigated conditions, moderate water deficit, severe water deficit, and post-rehydration recovery. According to the gene expression analyses, it is possible to observe that the CcMPR1, RBCS1, and CcGolS1 genes showed differential expression under the different water deficit conditions to which the genotypes were subjected, also showing that the majority of genotypes were able to recover after rehydration. The levels of organic nitrogen and proline were the biochemical parameters that showed the greatest differences among genotypes and could be used as markers of water stress, indicating the adoption of osmoregulation mechanisms in response to drought.